2018
DOI: 10.3390/polym10080814
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Research on Mechanical Properties of Bamboo Plastic Composites

Abstract: The focus of this study was to observe the mechanical properties of bamboo plastic composites (BPCs) with bamboo pulp fiber (BPF) or white mud (WM). The essential work of fracture (EWF) methodology was used to characterize the impact toughness of BPCs. The results revealed an increase in flexural, tensile and impact properties, when adding the BPF in the BPCs. While the flexural properties of WM-reinforced BPCs revealed increasing, there was a decrease in tensile and impact strength. In an impact strength anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…Their conclusions are confirmed by recent research [23,24]. The EWF testing on natural fiber reinforced polymer composites showed that we increased significantly with the amount of bamboo pulp fiber used in bamboo plastic composites but decreased with the increase of white mud in the bamboo plastic composites [25][26][27].…”
Section: Quasi-static Loading Modesupporting
confidence: 84%
See 1 more Smart Citation
“…Their conclusions are confirmed by recent research [23,24]. The EWF testing on natural fiber reinforced polymer composites showed that we increased significantly with the amount of bamboo pulp fiber used in bamboo plastic composites but decreased with the increase of white mud in the bamboo plastic composites [25][26][27].…”
Section: Quasi-static Loading Modesupporting
confidence: 84%
“…The EWF testing on natural fiber reinforced polymer composites showed that the impact fracture toughness (w e ) was increased by increasing fiber content. Many researchers [18]- [25]- [32] concluded that the presence of fiber can increase the energy that is anticipated during the fracture process.…”
Section: Dynamic Loading Modementioning
confidence: 99%
“…The impact performance test specimens included notched and unnotched samples. The results of the tests performed on the two types of samples were not significantly better than each other, but for the impact performance analysis of GF/PPS composites, the a cU values measured in the unnotched sample were the most conservative, so the unnotched sample was used, and the data were calculated in this paper [ 32 , 33 ]. The general equation for the impact strength of the unnotched sample is as follows: where is the impact strength of the unnotched supported beam, KJ/m 2 ; is the energy absorbed during the damage of the modified specimen, J; is the thickness of the sample, mm; and is the width of the model, mm.…”
Section: Methodsmentioning
confidence: 99%
“…A high intrinsic modulus of kenaf resulted in a stiffening effect in the biocomposites. The chain mobility and deformation ability of PLA and rubber matrices were restricted by dispersed kenaf particles (Ahmad and Baharum 2018;Xian et al 2018). However, the Alias et al (2020).…”
Section: Tensile Propertiesmentioning
confidence: 99%